ALGORITHMIC MECHANISMS IN ANTI-MONEY LAUNDERING SYSTEMS: A SYSTEMATIC REVIEW OF EFFECTIVENESS AND PERFORMANCE - Said, Roshima; Zolkaflil, Salwa; Che Adenan, Nur Zharifah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
This study provides a comprehensive review and classification of the current literature on algorithmic approaches for combating money laundering. A systematic literature review (SLR) was conducted using the Universiti Sains Malaysia (USM) Digital Library. After applying the inclusion and exclusion criteria, 27 relevant publications published between 2015 and 2020 were selected for analysis. A classification framework was developed to analyse the selected studies, which includes solutions, machine learning, data sources, assessment techniques, implementation tools, sampling approaches, and study regions. The findings provide insights into the current research landscape of algorithmic anti-money laundering (AML) systems and identify trends, gaps, and opportunities for future research.